EFFECTIVENESS OF TALENT ACQUISITION PROCESS IN INDIAN INDUSTRY - et al., Dr.K.Gunasekaran (International Journal of Advanced Science and Technology, 2019)
This research article objectives to attain essential to recruit people with requisite skills, qualification and experience keeping the present and future requirements. Competition among business industry for recruiting the best outstanding people has increased focus on innovation strategies, and management decision making process. Interviewer main aim to recruit only the talent candidates who would suit the firm culture, ethics and specific culture to the organization. The purpose of the research is to the current talent acquisition process in the organization and identify developing areas. Secondly, the project studies the extent of adoption of best practices in the firm. The research study also covers to evaluate the implementation of new and innovative methods in job analysis, recruitment, screening and selection processes in the industry. Descriptive research approach is applied in the study. Primary data is collected by means of direct interviews. The employees are quite satisfied with the current methodologies followed in the company and also agree that it is effective. The only suggestion is to uplift the effectiveness furthermore. The Employees agree that the talent acquisition process is effective and enable them in acquisitions the talents.